PENGARUH E-SERVICESCAPE TERHADAP TRUST DAN DAMPAKNYA PADA REPURCHASE INTENTION - Widiana, I Kadek; Kerti Yasa, Ni Nyoman (Buletin Studi Ekonomi, 2021)
This study aims to determine the effect of e-servicescape on trust and its impact on repurchase intention. The is all Tokopedia customers who live in Denpasar City who had already shopped at Tokopedia. The number of samples used was 120 respondents using the purposive sampling method. The data was collected by distributing questionnaires online via Google form. The data obtained were analyzed using data analysis techniques, namely Structural Equation Model (SEM) based on Partial Least Square (PLS) through the SmartPLS program. Based on the results of the research that has been conducted, it shows the following results: 1) aesthetic appeal has a positive and significant effect on trust, 2) layout and functionality has a positive and significant effect on trust, 3) financial security positively and significantly influences trust, 4) trust has a positive and significant effect on repurchase intention. The results of this study can be taken into consideration for Tokopedia in making strategies to increase consumer trust so that consumer repurchases can increase, especially through the e-servicescape section.